Distinct monoclonal antibodies separately label the hexons or the pentons of herpes simplex virus capsid. - Trus, B L (1992)
The surface shell of the capsid of herpes simplex virus type 1 (HSV-1) is 15 nm thick and 125 nm in outer diameter and has the form of an icosahedral (T = 16) surface lattice, composed of 150 hexons and 12 pentons. Hexons are traversed by axial channels and have six-fold symmetric external protrusions, separated by triangular nodules ("triplexes"). Pentons resemble hexons morphologically, apart from their different order of symmetry. To localize VP5, the major capsid protein, in the shell structure and to investigate whether pentons are composed of the same molecules as hexons, we have performed cryo-electron microscopy and three-dimensional image reconstructions of control HSV-1 B capsids and of B capsids immunoprecipitated with two monoclonal antibodies raised against purified VP5 and purified capsids. The results clearly map the epitope of the anti-VP5 monoclonal antibody to the distal tips of the hexon protrusions. In contrast, no detectable labeling of pentons was observed. We conclude that the hexon protrusions are domains of VP5 hexamers, other parts of these molecules forming the basic matrix of the capsid shell to which the other proteins are attached at specific sites. Conversely, the anti-capsid monoclonal antibody decorates the outer rim of pentons but does not bind to hexons. These observations imply that either pentons are composed of some other protein(s) or that they also contain VP5, but in a conformation sufficiently different from that assumed in hexons as to transform its antigenic character. Other evidence leads us to favor the latter alternative.